2017
DOI: 10.1097/qad.0000000000001405
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting combination anti-HIV drug suspension enhances and sustains higher drug levels in lymph node cells than in blood cells and plasma

Abstract: Objective:The aim of the present study was to determine whether a combination of anti-HIV drugs – tenofovir (TFV), lopinavir (LPV) and ritonavir (RTV) – in a lipid-stabilized nanosuspension (called TLC-ART101) could enhance and sustain intracellular drug levels and exposures in lymph node and blood cells above those in plasma.Design:Four macaques were given a single dose of TLC-ART101 subcutaneously. Drug concentrations in plasma and mononuclear cells of the blood (PBMCs) and lymph nodes (LNMCs) were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 15 publications
2
73
2
Order By: Relevance
“…This is relevant for lipid-based nanotherapeutic ARV delivery, based on subcutaneous administration. For example, lymphatic tissue localization of lipid-indinavir (IDV) particles via a passive diffusion strategy were explored [110][111][112][113][114].…”
Section: Increasing Access Of Drugs To Lymphoid Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is relevant for lipid-based nanotherapeutic ARV delivery, based on subcutaneous administration. For example, lymphatic tissue localization of lipid-indinavir (IDV) particles via a passive diffusion strategy were explored [110][111][112][113][114].…”
Section: Increasing Access Of Drugs To Lymphoid Tissuesmentioning
confidence: 99%
“…The mechanism causing the biodistribution of nanoparticles in the lymphatic system have been investigated [115]. Specifically, it was shown that nanoparticles administered subcutaneously were retained intra-lymphatically and subsequently distributed to the entire mouse body [114,115]. This effect was ascribed to the relatively large size of the molecules (60-120 nm) preventing extravasation from lymph vessels, which blocks release into the blood stream and enables transport from lymph node to lymph node through interconnected lymphatic vessels [115] (such effect shown in Figure 2).…”
Section: Increasing Access Of Drugs To Lymphoid Tissuesmentioning
confidence: 99%
“…However, as with the long-acting agents described above, this was a single agent formulation and presented resistance risks. We have since published studies on a similar nano-drug particle formulation containing three antiretroviral agents, with proven clinical efficacy and safety profiles, that are directed at two viral targets (protease and reverse transcriptase of HIV) in the presence of lipid excipients (DSPC and DSPE-mPEG 2000 ) [53,57]. In both reports, drug-lipid NP formulations were delivered via subcutaneous injection and relatively high concentrations of all three drugs in the HIV host cells of lymph nodes and blood were observed.…”
Section: Progression Of Drug Combination Nps To Primate and Human Tesmentioning
confidence: 99%
“…The ability to co-formulate drugs with disparate physical chemical characteristics and subsequently deliver them in a targeted manner in a fixed-dose combination represents significant progress in drug design and nanomedicine. With validated processes in place, and verified long-acting plasma and cellular pharmacokinetics, this anti-HIV drug combination nanoformulation is now referred to as TLC-ART 101 and is a candidate for further clinical development [57]. …”
Section: Progression Of Drug Combination Nps To Primate and Human Tesmentioning
confidence: 99%
See 1 more Smart Citation